Features of WTO Dispute Settlement. The Standing of the EU - Costin Horia Rogoveanu (Romanian Journal of European Affairs, 2010)
The WTO has an innovative system of dispute settlement, with the following features: sui-generis, integrated, resolving the disputes according to the WTO agreements, excluding unilateral solutions, interstate system. These features are detailed in the present article. Another level of analysis concerns the standing of the EU in the WTO, in general, and in the Geneva proceedings for dispute settlement, in particular. Generated by the quality of the European Communities statute as an original member of the Organisation, the EU has become one of the main users of the WTO dispute settlement system. One of the main challenges of the WTO dispute settlement mechanism is the implementation of decisions. In view of the cases assessed, while the execution record of the EU is a quite satisfactory one, it is apparent that implementation of decisions in more intricate cases creates difficulties at the Union level.